Role of the Qur'an in the transformation of human society - Sulaiman, Kabuye Uthman (Revelation and Science, IIUM, 2014)
There is no denying the fact that at one time in human history Muslims were the leaders in human values. They were the torchbearers of knowledge when other nations lived in darkness. They developed the physical aspect of human civilization by establishing libraries, hospitals and centers of learning. Today, however, Muslims are in a state of moral and intellectual decline. This paper argues that the primary cause of the advancement of the early Islamic society and the subsequent decline of Muslims is primarily due to the way the Qur’an has been dealt with. While the early Muslims read the Qur’an, understood it and acted upon its injunctions, today many Muslims read the Qur’an ritually, yet gaining nothing from it. The paper deals with two questions: Why the Qur’an quickly transformed the early Islamic community and not the present one? Why Muslims lost their supremacy in knowledge and morality?